2008
DOI: 10.1364/oe.16.009144
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the optical response of plasmonic nanoantennas

Abstract: Abstract:The optical properties of plasmonic dipole and bowtie nanoantennas are investigated in detail using the Green's tensor technique. The influence of the geometrical parameters (antenna length, gap dimension and bow angle) on the antenna field enhancement and spectral response is discussed. Dipole and bowtie antennas confine the field in a volume well below the diffraction limit, defined by the gap dimensions. The dipole antenna produces a stronger field enhancement than the bowtie antenna for all invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
320
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 410 publications
(327 citation statements)
references
References 54 publications
7
320
0
Order By: Relevance
“…This value approximates well the small substrateinduced frequency shift for nanoparticle plasmon resonances polarized parallel to a substrate. 33 The illumination is taken to be normal to the nanostructure plane, with polarization along the antenna axis.…”
Section: Resultsmentioning
confidence: 99%
“…This value approximates well the small substrateinduced frequency shift for nanoparticle plasmon resonances polarized parallel to a substrate. 33 The illumination is taken to be normal to the nanostructure plane, with polarization along the antenna axis.…”
Section: Resultsmentioning
confidence: 99%
“…For larger antennas with complicated shapes, such as those shown schematically in Figure 1.11(a), the description via an analytic model is quite difficult, and numerical simulation methods based on the solution of Maxwell's equations have to be applied to calculate their optical properties. Specifically, for bow-tie antennas, the resonance frequency and also the field enhancement are critically dependent on the particular shape and can be tuned by the variation of the length h, opening angle Ξ , thickness t, and gap size d, as well as the choice of the substrate for the bow-tie fabrication [45,42].…”
Section: Plasmonic Nanostructures For Field Enhancementmentioning
confidence: 99%
“…The optimization of the evaporation conditions improved the surface roughness (measured by the root-mean-squared (RMS) value of the surface height) and enabled the fabrication of high quality nanoantennas. Plasmonic nanostructures offer unique possibilities for enhancing linear and nonlinear optical processes [45,50,51,52,53,6]. Recently, Kim et al [24] reported nanostructure-enhanced high harmonic generation (HHG).…”
Section: Home-built Vacuum Setup For Euv Light Generation and Spectramentioning
confidence: 99%
“…[10][11][12] Moreover, the resonance frequency of plasmonic dipole antennas can be tuned to a desired value by varying the antenna length or gap size, providing additional design flexibility. 13 While the emphasis of the present publication is on trapping nanoscopic objects in the gap of the antenna, let us mention that microscopic cells have been trapped using the field generated by the whole plasmonic antenna by Righini et al 14 In addition to an enhanced trapping force, a plasmonic antenna can also be used to monitor in real time the trapping events from nonfluorescent nanoparticles, including particles as small as 10 nm. Actually, there is still today a lack of rapid and noninvasive methods for the detection of small nonfluorescent nanoparticles, although this detection is important for many practical applications.…”
mentioning
confidence: 99%